Factors Associated with High-Alert Medication (HAM) Knowledge of Pharmaceutical Staff at Tangerang Regional Hospital, Indonesia - Sherly Tandi Arrang; Devina Clara Alverina; Dion Notario (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: High-alert medication (HAM) poses a high risk of causing serious harm to patients when used incorrectly. One of the critical strategies to reduce or prevent medication errors associated with medication is ensuring adequate knowledge among healthcare providers.Objectives: This study aims to assess knowledge level of pharmaceutical staff regarding HAM in hospital settings.Methods: An observational, non-experimental design was used with a cross-sectional approach. Data were collected with structured questionnaires and analyzed through multiple linear regression.Results: A total of 89 respondents participated in the study, of which 97% demonstrated a good understanding of HAM. The mean ± SD value of respondents was 87.97 ± 8.50, while the minimal, maximal, and median values were 64.71, 100, and 88.24, respectively. Multivariate analysis showed that variables such as age, gender, education level of pharmacy technicians, and work experience (p > 0.05) were not significantly associated with knowledge level. However, the education level of pharmacists indicated a statistically significant association (p < 0.05) with knowledge regarding HAM.Conclusion: This study found a significant association between the education level of pharmacist staff and knowledge level. Future studies should consider various hospital settings across Indonesia to gain a more comprehensive understanding regarding knowledge level of pharmaceutical staff concerning HAM. Additionally, further investigations are needed to explore the correlation between the incidence of medication errors associated with HAM and knowledge level of pharmaceutical staff.